Trajetória da empresa e evolução das práticas de inovação de produto e processo: o caso das empresas do Complexo Petroquímico de Triunfo - Sá, Ubiratan Gomes de Carvalho (Universidade do Vale do Rio dos Sinos, 2012)
Trajectories of firms studies’ seek to identify the reasons for their longevity through the relevant factors of being competitive in long periods of time. The ones intensive in capital and technology have technological innovation practices subordinated to strategy due to its importance for the firm performance. The petrochemical companies fit this description. They are also important for both national and regional economic activity by the upstream presence in several supply chains, since they provide raw material for other manufacturing industries, their strategic place at downstream petroleum refining and natural gas use, and through active participation in national trade accounts by exporting products and importing materials and equipment. Companies located at Triunfo Petrochemical Complex in Rio Grande do Sul, Brazil went through several episodes of turbulence which transformed their structures. These coincide roughly with changes in the economic environment and regulatory events such as economic downturns, worldwide consolidation of chemical and petrochemical industry, and emergence of new and cheaper complementary technologies. To understand these changes and impacts on the technological innovation practices were evaluated a set of theories that attempt to explain the factors influencing firm’s competitiveness. The chosen approach was the Theory of Punctuated Equilibrium by considering companies’ evolution as a result of the dynamics among external and internal factors that trigger structural changes generating turbulence followed by a brief period of relative stability in which these transformations are consolidated. A qualitative study was conducted in four companies currently operating in the Triunfo Petrochemical Complex using the multiple case study methodology. The data collection and analysis covering the time interval from the start of operations until 2011 indicate the existence of turbulence for three times and two periods of stability. This research can contribute on confirming the Theory of Punctuated Equilibrium use for longitudinal studies of companies’ trajectory, not only for short periods of time. Comparison with other similar studies may contribute to the development of this theory.
Keywords: Teoria do equilíbrio pontuado; Petroquímica; Inovação tecnológica; Trajetória; Theory of punctuated equilibrium; Petrochemical; Technological innovation; Trajectory; ACCNPQ::Ciências Sociais Aplicadas::Administração